Climate finance can unlock the full potential of circular bioeconomy - Bodach, Susanne; Perera, Thinuri (International Water Management Institute, 2025)
The Circular Bioeconomy (CBE) provides a critical solution to climate change and resource scarcity by shifting from a linear to a circular model that reuses and regenerates biological materials. This approach reduces greenhouse gas (GHG) emissions through methods like converting organic waste into bioenergy and fertilizers. Furthermore, wastewater reuse at scale has huge climate adaptation benefits. Scaling of CBE solutions requires significant financial investment and needs to leverage mechanisms such as carbon credits and international climate funds. Along with supportive policies the full tranistion towards a more Circular Bioeconomy has the potential for building more resilient economies and achieving sustainable livelihoods in Lower and Middles Income countries.